Food allergy quality of life and living with food allergy. Issue 3 (June 2016) - Greenhawt, Matthew
Abstract : Purpose of review: Food allergy quality of life (QoL) has emerged as a key outcome to understand how food-allergic individuals and their families live with disease. Food allergy QoL has been measured since the early 2000's, but in the past 10–12 years, the advent of disease-specific indices has better defined the daily psychological burden of living with disease, which is distinct from measuring quality life in other chronic illnesses where affected patients suffer from more physical symptoms which may cause measurable shifts in disease status. Recent findings: Multiple recent studies from the United States, Europe, and Australia have better detailed relationships between food allergy QoL and key aspects, such as the individual food allergen, allergic comorbidity, reaction severity, reaction treatment, social determinants of health status, health beliefs and reaction perception, individual facets of the individual or caregiver, potential disease treatment, and disease management. With the advent of clinical trials of potentially disease treating or curative therapy, QoL has become a central outcome to demonstrate the efficacy of such potential products. Summary: Though food allergy QoL has emerged as a recognized outcome, more is needed to enhance life with disease, and the field lacks specific tools beyond potential therapies to target and help repair poor QoL in patients and their caregivers.